2003
DOI: 10.1002/adsc.200390020
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Linear Effect of Modifier Composition on Enantioselectivity in Asymmetric Hydrogenation over Platinum Metals

Abstract: Prominent non-linear behavior was observed when mixtures of cinchona alkaloids were applied as chiral modifiers in enantioselective hydrogenations over Pt/Al 2 O 3 and Pd/TiO 2 . The phenomenon is traced to differences in the strength and geometry of alkaloid adsorption on the metal surface. In ethyl pyruvate hydrogenation under close to ambient conditions the weaker adsorbing quinidine (QD) outperformed the generally preferred modifier cinchonidine (CD) and afforded the highest ee (96 ± 98%) at 1 ± 5 bar. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 43 publications
1
41
0
1
Order By: Relevance
“…In agreement with studies employing a variety of instrumental methodologies, it appears that in the concentration range allowing high ee to be attained (0.01-0.1 mmol L )1 ) the quinoline skeleton of CD is approximately parallel to the Pt surface [24,[27][28][29], whereas the plane of the quinoline skeletons of CN and QD is tilted relative to the Pt surface. Q may take an intermediate position, i.e.…”
Section: Results Of Modifier Mixturessupporting
confidence: 69%
“…In agreement with studies employing a variety of instrumental methodologies, it appears that in the concentration range allowing high ee to be attained (0.01-0.1 mmol L )1 ) the quinoline skeleton of CD is approximately parallel to the Pt surface [24,[27][28][29], whereas the plane of the quinoline skeletons of CN and QD is tilted relative to the Pt surface. Q may take an intermediate position, i.e.…”
Section: Results Of Modifier Mixturessupporting
confidence: 69%
“…It has been shown that the non-linear behaviour of modifier mixtures in Pt-and Pd-catalyzed hydrogenation reactions are basically due to their different adsorption strengths on the metal surface. [5,21,51,52] Apparently, 18 cannot compete with cinchonine for the Pt surface sites and thus can barely influence the enantiodifferentiation during hydrogenation of KPL.…”
Section: Full Papersmentioning
confidence: 98%
“…The two most important asymmetric catalyst types are platinum catalyst modified with cinchona alkaloids and related modifiers, successful for α-functionalized ketones such as hydrogenation of ethyl pyruvate to ethyl acetate over cinchona-modified with ee's up to 98% and palladium catalysts modified with cinchona alkaloids which achieve ee's up to 94% for selected activated C=C bonds such as partial hydrogenation of a 4-methoxy-6-methyl-2-pyrone over cinchona-modified [32,33].…”
Section: Entrymentioning
confidence: 99%